A survey of canine respiratory pathogens in New Zealand dogs. Issue 5 (3rd September 2018) - Sowman, HR; Cave, NJ; Dunowska, M
Abstract: AIMS: To determine which of the common canine respiratory pathogens circulate among selected populations of healthy and diseased dogs in New Zealand. METHODS: Coagulated blood samples for serology and oropharyngeal swabs for virology were collected from healthy dogs (n=47) and from dogs with acute respiratory disease (n=49). For diseased dogs a convalescent blood sample was also collected 3–4 weeks later. Oropharyngeal swabs were subjected to virus isolation and tested for canine parainfluenza virus (CPIV), canine adenovirus (CAdV) 2, canine herpesvirus (CHV), canine respiratory coronavirus (CRCoV), canine influenza virus (CIV), canine distemper virus (CDV), Bordetella bronchiseptica, Streptococcus equi subsp. zooepidemicus, and Mycoplasma cynos nucleic acids by quantitative PCR (qPCR). Sera were tested for CRCoV antibody using competitive ELISA and results expressed as percent of inhibition (POI). RESULTS: The mean age of diseased dogs (2.7, min <0.5, max 8.5 years) was lower than the mean age of healthy dogs (5.3, min <0.5, max 17 years) (p<0.001). In total, 20/94 (21%) dogs were positive for at least one agent by qPCR. Diseased dogs were most commonly positive for M. cynos (8/47, 17%), followed by CPIV (3/47, 6%) and B. bronchiseptica (3/47, 6%), while healthy dogs were most commonly positive for CAdV-2 (6/47, 13%), followed by M. cynos (2/47, 4%). All samples were negative for CIV, CRCoV, CDV and S. equi subsp. zooepidemicus . Viruses were not isolated from any of the samples tested. In total, 47/93 (50%) dogs were seropositive for CRCoV on at least one sampling occasion. Samples from diseased dogs were more frequently seropositive for CRCoV, with higher POI, than samples from healthy dogs. CONCLUSIONS AND CLINICAL RELEVANCE: We showed that CAdV-2, CPIV, CHV, CRCoV, B. bronchiseptica and M. cynos circulated among sampled dogs. The convenience sampling methodology, with a poor match between the populations of diseased and healthy dogs in terms of age, breed and use, together with the relatively small sample size precluded inference of any causal relationships between infection with a given pathogen and development of disease. None-the-less, our data suggest that further investigation into epidemiology and disease association of CRCoV and M. cynos is warranted. In addition, circulation of novel respiratory pathogens among dogs in New Zealand should be considered in future studies, as 70/94 (74%) diseased dogs were negative for all the pathogens tested.